Livestock management information system - Wan Arif, Wan Abdul Hafiz; Hassan, Sa'adah; Admodisastro, Novia Indriaty; Che Pa, Noraini (University Community Transformation Centre, Universiti Putra Malaysia, 2017)
Livestock Management Information System (Livestock MIS) is an electronic information system which allows users to manage their livestock. The main purpose of this system is to increase and optimize livestock management to a new level, especially in Malaysia. Most farmers in Malaysia opt to use the traditional way of managing livestock which involves paper filing. This method is inefficient as it requires more time and effort to accomplish tasks. Besides that, farmers also have difficulty to create report as reports need data to be calculated and analyzed. Among the common reports produced are milk production analysis, health analysis and vaccination reports. Besides that farmers also need to calculate feed formulation for the livestock and its expected carcass. All of these tasks are tedious. Thus, the Livestock MIS is proposed to ease farmers in terms of managing and monitoring their livestock. It is aimed that the emergence of the Livestock MIS will revolutionize the way farmers managing livestock and will increase the productivity. The system development methodology used to develop this system was Rapid Application Development (RAD).